The Pathophysiology of H2S in Renal Glomerular Diseases - Karl-Friedrich Beck; Josef Pfeilschifter (Biomolecules, 2022)
Renal glomerular diseases such as glomerulosclerosis and diabetic nephropathy often result in the loss of glomerular function and consequently end-stage renal disease. The glomerulus consists of endothelial cells, mesangial cells and glomerular epithelial cells also referred to as podocytes. A fine-tuned crosstalk between glomerular cells warrants control of growth factor synthesis and of matrix production and degradation, preserving glomerular structure and function. Hydrogen sulfide (H2S) belongs together with nitric oxide (NO) and carbon monoxide (CO) to the group of gasotransmitters. During the last three decades, these higher concentration toxic gases have been found to be produced in mammalian cells in a well-coordinated manner. Recently, it became evident that H2S and the other gasotransmitters share common targets as signalling devices that trigger mainly protective pathways. In several animal models, H2S has been demonstrated as a protective factor in the context of kidney disorders, in particular of diabetic nephropathy. Here, we focus on the synthesis and action of H2S in glomerular cells, its beneficial effects in the glomerulus and its action in the context of the other gaseous signalling molecules NO and CO.